2010
DOI: 10.1016/j.neuropsychologia.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Exceptions and anomalies: An ERP study on context sensitivity in autism

Abstract: Several studies have demonstrated that people with ASD and intact language skills still have problems processing linguistic information in context. Given this evidence for reduced sensitivity to linguistic context, the question arises how contextual information is actually processed by people with ASD. In this study, we used event-related brain potentials (ERPs) to examine context sensitivity in high-functioning adults with autistic disorder (HFA) and Asperger syndrome at two levels: at the level of sentence p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 51 publications
(72 reference statements)
7
64
3
1
Order By: Relevance
“…Here, we show that this lack of sensitivity is not specific to linguistic targets, but is also observed when the target is a picture. As reported in Pijnacker et al [10] for a different task, we found larger LPP amplitude in the ASD group compared with controls for incongruent targets: our results generalize this effect to both verbal and musical priming. Participants identified the incongruent stimuli after verbal cues at a similar rate, despite the insensitivity of the N400 and abnormal modulation of the LPP.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Here, we show that this lack of sensitivity is not specific to linguistic targets, but is also observed when the target is a picture. As reported in Pijnacker et al [10] for a different task, we found larger LPP amplitude in the ASD group compared with controls for incongruent targets: our results generalize this effect to both verbal and musical priming. Participants identified the incongruent stimuli after verbal cues at a similar rate, despite the insensitivity of the N400 and abnormal modulation of the LPP.…”
Section: Discussionsupporting
confidence: 91%
“…There is general consensus that the N400 amplitude is reduced in ASD patients, suggesting disrupted neuronal responses to semantic mismatch, but considerable controversy remains over the presence and interpretation alterations in another, related but distinct potential, called the late positive potential (LPP) [4,9,10]. This component is typically taken as an index of late integrative and reanalysis processes, and memory formation [11]; however, recent work on semantic violations has led to the hypothesis that the LPP in this patient group may particularly reflect semantic processing [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the enhanced late positivity for the incongruent words is larger parietally than frontally. Data fromPijnacker et al, 2010; we thank Dr. Judith Pijnacker for providing an adaptation of the figure appearing in the published work.…”
mentioning
confidence: 99%
“…Other studies cited by the contributions as evidence that autistic persons have a specific deficit in figurative language rely precariously on Verbal or Performance IQ for their studies’ control (e.g., Eales 1993; Ghaziuddin et al 2000; Gold & Faust, 2010; Gold, Faust, & Goldstein, 2010; Just, Cherkassky, Keller, & Minshew, 2004; Jolliffe & Baron-Cohen, 1999a; 1999b; Kana, Keller, Cherkassky, Minshew, & Just, 2006; Kleinhans, Müller, Cohen, & Courchesne, 2008; Losh & Capps, 2003; Paul & Cohen, 1985; Pijnacker, Geurts, van Lambalgen, Buitelaar, & Hagoort, 2010; Tesink, Buitelaar, Petersson, van der Gaag, Kan, Tendolkar, & Hagoort, 2009; Wang, Lee, Sigman, & Dapretto, 2006; 2007). …”
mentioning
confidence: 99%